Constructing Multi‐Stimuli‐Responsive Luminescent Materials through Outer Sphere Electron Transfer in Ion Pairs. Issue 8 (27th January 2019) - Ma, Yun; Shen, Liang; She, Pengfei; Hou, Yuqi; Yu, Yaxin; Zhao, Jianzhang; Liu, Shujuan; Zhao, Qiang
Abstract: Stimuli‐responsive luminescent materials are of scientific and technological interest due to their wide range of optoelectronic applications. The utilization of photoinduced electron transfer (PET) reactions is an effective strategy to design various stimuli‐responsive luminescent materials. To date, most of these materials are based on the inner sphere electron transfer mechanism, which refers to a redox chemical reaction that proceeds via a covalent bridge. In contrast, the method of using outer sphere electron transfer mechanism is superior to the covalent approach as it does not require tedious synthesis. Ion pairs, which are composed of two oppositely charged components, are ideal for the development of stimuli‐responsive materials based on outer sphere electron transfer mechanism. Here, it is demonstrated that the emission intensity of an ion pair, consisting of an electron‐deficient phosphor ([Ir(ttpy)2 ] 3+, ttpy = 4′‐(p‐tolyl)‐2, 2′:6′, 2″‐terpyridine) and an electron‐rich quencher (BH4 −, tetrabutylammonium borohydride), is significantly enhanced by applying an electrical stimulus or under UV light irradiation. As far as it is known, this work represents the first example of luminescent material showing smart responses to both electrical and light stimuli. The present results indicate that the use of suitable ion pairs can pave the way toward the construction of multi‐stimuli‐responsive smart materials through outer sphere electron transfer mechanism. Abstract : An effective strategy is reported to construct novel multi‐stimuli‐responsive luminescent materials that utilize the outer sphere electron transfer mechanism. Specifically, it is demonstrated that the emission intensity of an ion pair, consisting of an electron‐deficient iridium(III) complex and an electron‐rich tetrabutylammonium borohydride, is significantly enhanced by applying a voltage or UV light irradiation.